Subnational Variations in Government-Nonprofit Relations: A Comparative Analysis of Regional Differences within Russia. Issue 1 (2nd January 2020) - Toepler, Stefan; Pape, Ulla; Benevolenski, Vladimir
Abstract: This article discusses the evolution of government-nonprofit relations at the regional level in Russia against the background of national-level restrictions on NGOs. Russia recently also introduced supportive policies and the article aims to trace the regional administrations' reactions to the dual realities of the federal government's posture towards nonprofits. Considerable variation was found in regional government-nonprofit relationships as well as deviation from national policy stances. Using a subnational comparative framework, this article addresses a gap in the literature and lays the groundwork for future cross-national comparisons of subnational variations of government-nonprofit relations in other authoritarian and hybrid political regimes.